Urban Public Transport: Planning Principles and Emerging Practice. (August 2017) - McLeod, Sam; Scheurer, Jan; Curtis, Carey
This article reviews the literature on current "best practice" principles for planning public transport (PT) networks within the context of planners seeking to transition their cities toward sustainable mobility. An overview is provided of the history of ideas about network development. The emerging frontiers for multimodal, demand-responsive PT and the potential implications of new transport technology on traditional PT are discussed. The future role of transit-oriented development within PT network structures is considered. The "moderators" to network design that may impede future best practice brings the article to conclusion.